ENHANCING STUDENTS’ CREATIVE AND COMPOSITIONAL THINKING THROUGH INNOVATIVE PEDAGOGY - Jalolov Shavkat Choriyevich, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article examines the role of innovative pedagogical approaches in enhancing students’ compositional and creative thinking in art education. It focuses on the application of digital tools, project-based learning, flipped classrooms, and interactive platforms to improve students’ artistic competencies, problem-solving abilities, and critical thinking. The research highlights practical strategies for integrating technology into classroom practice to develop students’ independent and analytical skills.